Analysis of the dynamics of mortality from respiratory diseases in the Russian Federation for 2019–2020 - Oksana M. Drapkina; Irina V. Samorodskaya; Elena V. Bolotova; Anna V. Dudnikova (Терапевтический архив, 2022)
Aim. To study the dynamics and contribution of mortality from Diseases of the respiratory system (DRS) in 2019 and 2020 to mortality from all causes with and without deaths from COVID-19 in 82 regions of the Russian Federation.